Complex Innovation Policy in Kazakhstan with the New Legal Regulations: Key Issues and Challenges - SAIYMOVA, Meiramkul; SEISINBINOVA, Almira; DAULETOVA, Rysgul; ISKAKOV, Sanimzhan; SULEIMENOVA, Buldyryk; BEKBULATOVA, Rakhima; KABDULLINA, Gulmira (Journal of Advanced Research in Law and Economics, 2019)
Since gaining independence, Kazakhstan has been experiencing internal and external economic crises due to the nature of its economy, which relies on the oil and gas sector. To transform and drive national economic development, Kazakhstan has adopted policies and several strategic documents that aim to boost innovation activities, particularly in the industrial sector. This paper aims to review and analyze the national innovation policy in Kazakhstan, showing the three main practical problems that Kazakhstan faces with the implementation of the innovation policy in context of the ‘Dutch disease’.